Psychosocial risks as predictors of drug use in Mexican university students of Health Sciences - Beverido Sustaeta, Paulina; Salas García, Betzaida; Gogeascoechea Trejo, María del Carmen; De San Jorge Cárdenas, Xóchitl; Cruz Juárez, Alma de los Ángeles (Pensando Psicología, 2020)
Considering the future personal health and professional performance of Health Sciences students, it is important to learn about their use of psychoactive drugs. Objective: To determine whether psychosocial risk factors (consumption intention, use of leisure time, anxiety and depression symptoms) are predictors (OR) of the consumption of legal, illegal and medical drugs or non-prescription drugs in the Health Sciences student population. Method: Quantitative, descriptive, epidemiological, voluntary and anonymous cross-sectional online survey of 5,881 students of the Health Sciences division of a Mexican public university. Results: Psychology students had the highest prevalence of consumption while nursing students had the lowest in all drugs except cocaine, whose prevalence in the last month showed the highest percentage. Most students had a low level of nicotine dependence. In terms of alcohol and marihuana use, psychology and nutrition students reported the highest percentages in the high-risk consumption category. It was found that psychology students are more likely to consume marihuana than all the other Health Sciences division students. Nutrition students presented a greater possibility of cocaine consumption than psychology students. Conclusions: The predictive factors that were associated with the consumption of tobacco, alcohol, non-prescription drugs, marihuana, and cocaine were: the study program, anxiety, and behavioral intention. The presence of anxiety symptoms was shown as a predictor of the consumption of all drugs, while depression symptoms were associated with the consumption of tobacco, alcohol and non-prescription drugs.